Turkish Academics as Neoliberal Subjects? - Sener, Meltem (Sage Publications India Pvt Ltd, 2012)
A university is an institution that has been extensively restructured according to the market logic with the process of neoliberal globalization. As the resources for doing research are limited especially in the developing countries, the funds provided for research by institutions such as the World Bank gain importance for the academics. This article demonstrates how the academics' experience of producing knowledge for the World Bank fosters the neoliberalization of the university in Turkey. Depending on interviews with academics, the article looks at the impacts of doing research for the World Bank. It concludes that although these academics are forced to act as entrepreneurial subjects, they have not necessarily internalized this neoliberal mentality.
Keywords: Neoliberal Governmentality; World Bank; University; Turkish Academics; Knowledge Production; World-Bank; Knowledge; Identities; Liberalism; Critique